DETECTION OF YEAST STRAINS IN CHROME TANNED LEATHER AND SHOES - (:unkn) unknown (AMER LEATHER CHEMISTS ASSN, 1992)
Turkish sole leather, chrome tanned leather, new shoes, used shoes and skin swabs from the feet of people who wore the shoes were all examined in this study for yeast. Candida albicans, Candida parapsilosis, Candida guilliermondii, Candida lusitaniae, Candida pseudotropicalis, Candida krusei, Candida famata, Saccharomyces cerevisiae, Rhodotorulla species, Exophila jeanselmei, Phaeococcomyces species, Aureobasidium pullulans, Geotrichum candidum, and Wallemia sebi were isolated from these various leather specimens and people's feet. The flora found on used shoes and that of the samples taken from people's feet were very similar as expected. Somewhat surprising, however, was that a very similar flora was found on new shoes. This suggests strongly that contamination of new shoes occurs during processing and storage. This contamination is a possible cause of mycotic infection of the individuals who purchase these shoes. Sole leather and chrome tanned leathers contained fewer yeast strains and these also might contribute to the contamination of shoes. Candida albicans, Rhodotorulla species, Candida parapsilosis, Saccharomyces cerevisiae, Candida guilliermondii were the most common species isolated.